Bioprocess engineering for biohythane production from low-grade waste biomass: technical challenges towards scale up. (April 2018) - Liu, Zhidan; Si, Buchun; Li, Jiaming; He, Jianwei; Zhang, Chong; Lu, Yuan; Zhang, Yuanhui; Xing, Xin-Hui
Graphical abstract: Highlights: Identify the importance of sustainable hythane fuel via biological process. Compare biohythane with other biological processes for bioenergy production. Advantage of biohythane over biogas are improved energy recovery and reduced fermentation time. Highlight and comment the technical issues towards scale up of biohythane system. Bioprocess control and utilization of products are practical challenges. Abstract : A concept of biohythane production by combining biohydrogen and biomethane together via two-stage anaerobic fermentation (TSAF) has been recently proposed and considered as a promising approach for sustainable hythane generation from waste biomass. The advantage of biohythane over traditional biogas are more environmentally benign, higher energy recovery and shorter fermentation time. However, many of current efforts to convert waste biomass into biohythane are still at the bench scale. The system bioprocess study and scale up for industrial application are indispensable. This paper outlines the general approach of biohythane by comparing with other biological processes. The technical challenges are highlighted towards scale up of biohythane system, including functionalization of biohydrogen-producing reactor, energy efficiency, and bioprocess engineering of TSAF.